The Time Course of Emotion Effects in First and Second Language Processing: A Cross Cultural ERP Study with German–Spanish Bilinguals - Conrad, Markus; Recio, Guillermo; Jacobs, Arthur M. (Frontiers in Psychology, 2011)
To investigate whether second language processing is characterized by the same sensitivity to the emotional content of language – as compared to native language processing – we conducted an EEG study manipulating word emotional valence in a visual lexical decision task. Two groups of late bilinguals – native speakers of German and Spanish with sufficient proficiency in their respective second language - performed each a German and a Spanish version of the task containing identical semantic material: translations of words in the two languages. In contrast to theoretical proposals assuming attenuated emotionality of second language processing, a highly similar pattern of results was obtained across L1 and L2 processing: ERP waves generally reflected an early posterior negativity plus a late positive complex for words with positive or negative valence compared to neutral words regardless of the respective test language and its L1 or L2 status. These results clearly suggest that the coupling between cognition and emotion does not qualitatively differ between L1 and L2 although latencies of respective effects differed about 50ms. Only Spanish native speakers currently living in the L2 country showed no effects for negative as compared to neutral words presented in L2 potentially reflecting a predominant positivity bias in second language processing when currently being exposed to a new culture.